UTILIZATION OF HERBAL EXTRACTS AS ALTERNATIVE ANTIPARASITIC AGENTS IN CULTURED FISH: A REVIEW - Nurfitri Rahim (Universitas Mataram, 2025)
Parasitic infections represent one of the major constraints in fish aquaculture, causing reduced growth performance, survival rates, and significant economic losses. Current parasite control strategies largely rely on synthetic chemicals, which may lead to residue accumulation, parasite resistance, and negative environmental impacts. Therefore, safer and more sustainable alternatives are urgently needed. This review aims to evaluate the potential of herbal extracts as alternative antiparasitic agents in fish culture based on available scientific evidence. A systematic descriptive literature review was conducted using databases including Google Scholar, ResearchGate, Scopus, and SINTA. A total of 13 publications that met the inclusion criteria were analyzed based on the type of herbal material, fish species tested, target parasites, application methods, effectiveness, and mechanisms of action. The results indicate that various herbal extracts exhibit high antiparasitic efficacy against a wide range of fish ectoparasites in both in vitro and in vivo studies. The antiparasitic activity is mainly associated with bioactive compounds such as terpenoids, flavonoids, alkaloids, phenolics, and essential oils, which act through membrane disruption, interference with the nervous system, and inhibition of parasite metabolism and attachment. Overall, this review concludes that herbal extracts have strong potential as environmentally friendly antiparasitic alternatives in aquaculture; however, their practical application requires further standardization of dosage, application methods, and field-scale validation to ensure efficacy and safety in commercial production systems.